2005
DOI: 10.1111/j.0958-7578.2005.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Amotosalen photochemical inactivation of severe acute respiratory syndrome coronavirus in human platelet concentrates

Abstract: A novel human coronavirus causing severe acute respiratory syndrome (SARS) emerged in epidemic form in early 2003 in China and spread worldwide in a few months. Every newly emerging human pathogen is of concern for the safety of the blood supply during and after an epidemic crisis. For this purpose, we have evaluated the inactivation of SARS-coronavirus (CoV) in platelet concentrates using an approved pathogen inactivation device, the INTERCEPT Blood System. Apheresis platelet concentrates (APCs) were inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…These studies showed that PCT with amotosalen and UVA light is effective against a broad range of pathogens in plasma. This finding is not surprising based on the pathogen inactivation efficacy previously demonstrated for PLTs with the same dose of amotosalen and same dose of UVA light 15‐20 . The levels of inactivation for representative viruses, bacteria, and protozoa were measured with PCT conditions developed for the commercial application of FFP.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These studies showed that PCT with amotosalen and UVA light is effective against a broad range of pathogens in plasma. This finding is not surprising based on the pathogen inactivation efficacy previously demonstrated for PLTs with the same dose of amotosalen and same dose of UVA light 15‐20 . The levels of inactivation for representative viruses, bacteria, and protozoa were measured with PCT conditions developed for the commercial application of FFP.…”
Section: Discussionsupporting
confidence: 54%
“…Thus PCT has the potential to inactivate new and emerging enveloped viruses and prevent them from entering the blood supply. Indeed, it was found that SARS‐CoV was inactivated by PCT in both PLTs and plasma 15 …”
Section: Discussionmentioning
confidence: 99%
“…The inactivation mechanism combines the nucleic acid-intercalating property of amotosalen with its cross-linking capabilities after UVA activation to eliminate the replicative function of treated pathogens. PCT has been shown to inactivate a broad spectrum of viruses, bacteria, parasites, and white blood cells and create safer blood-transfusion products [11,12,[14][15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…Finally, it should be pointed out that the bacterial testing approach is limited only to the detection of bacteria. The pathogen inactivation of PLT has been shown to be effective in inactivating viruses, 38‐40 protozoa, 41,42 and WBCs, 43 in addition to bacteria, thus providing a more comprehensive approach to transfusion safety.…”
Section: Discussionmentioning
confidence: 99%